Collaborative Process for Evaluating Education Technology In School - Widhanarto, Ghanis Putra; Sukirman, Sukirman; Prihatin, Titi; Sulistio, Basuki; Iriyanti, Novita Trisna (Lembaran Ilmu Kependidikan, 2019)
The purpose of this study is to uncover a collaborative process of educational technology in schools, they call evaluating, decision making, and applying. Through qualitative methods revealed how evaluative processes can include interdisciplinary stakeholders, and then to explore the process of applying technology in school in the context of teaching and learning in real terms on subjects. The research design begins with the identification of learning activities, the development of evaluation criteria that maps the objectives of learning activities and the needs of policy makers, and the interventions of educational technology activities in the teaching and learning process. The results of the study are identified evaluation methods that involve collaborating interdisciplinary stakeholders on teacher teaching abilities for the purpose of exposing several divergent perspectives and views. The implication for academics who need pedagogical is the exposure of patterns and completeness of administrative support.